TRANSLATION QUALITY POLICY IN THE EUROPEAN PARLIAMENT (CASE OF TRANSLATION INTO THE FRENCH LANGUAGE) - Olefir, Hanna; Deineko, Ivan; Deineko, Iryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article provides overview of the EU citizens’ access to legal and key political documents in their respective state languages. We have described the phenomenon of employing the so-called intermediary “relay” languages in cases when it does not seem possible to provide translation in all 276 possible combinations of language pairs. The article offers analysis of major basic requirements to an interpreter/translator, his or her thematic, professional and linguistic competences, as well as practices of translation/interpretation, which enable the proper quality of parliamentary documents translation. By thematic competences we mean being well versed in politics, economics and finance, law and management, science and technology, the EU institutions and procedures. Linguistic competences imply proficiency in one’s native language, its stylistic aspects, advanced level and complete passive comprehension of at least two other official languages of the EU. Professional competences of a translator imply that he or she can fully comprehend the texts in the source language and stylistically accurately render them in target language, as well as quickly find the necessary terms or facts in both languages, efficiently use machine translation, if necessary. We have identified the logical sequence of translating the texts on parliamentary activities, which are interrelated with one another. The article also dwells on the role of machine translation, translator/interpreter’s memory, source of reference, internal electronic databases in the process of translation. We have cited certain examples of complicated cases and challenges in translation (motivated by gender or historically), as well as text form (punctuation, typography). ____________ References • European Parliament, access http://www.europarl.europa.eu • Guide à l’usage des linguistes et des assistantes de traduction, access http://publications.europa.eu/code/fr • Profil du traducteur, access https://ec.europa.eu/info/jobs-european-commission/working-eu/translator-profile_fr • Quality Control Guidelines Ex-ante and ex-post quality checks in DG Translation, access http://www.europarl.europa.eu/ portal/en • Quality Manual DG Translation, access http://www.europarl.europa.eu/portal/en • Translation services – Requirements for translation services, access https://www.iso.org/standard/59149.html